Oxidative Stress and Abnormal Tendon Sonographic Features in Elite Soccer Players (A Pilot Study) - Abate, Michele; Di Carlo, Luigi; Cocco, Giulio; Cocco, Antonino; Sabatini, Ernesto; Salini, Vincenzo (Revista Brasileira de Ortopedia, 2021)
Objective Sound experimental data suggest that oxidative stress plays an important role in the pathogenesis of tendinopathies. However, this hypothesis in humans remains speculative given that clinical data are lacking to confirm it. Recently, a new methodology has allowed to quantify the oxidative stress in vivo by measuring the concentration of hydroperoxides of organic compounds, which have been utilized as an oxidative stress-related marker in several pathologic and physiologic conditions. Given the reliability of this test and the lack of information in subjects with tendinopathies, the aim of the present study was to assess the oxidative stress status in elite professional soccer players with and without ultrasonographic features of tendon damage.Methods In 73 elite players, blood metabolic parameters were evaluated and oxidative stress was measured by means of a specific test (expressed as U-Carr units). Therefore, an ultrasonographic evaluation of the Achilles and patellar tendons was performed.Results No significant relationships were observed between metabolic parameters and oxidative stress biomarkers. The Achilles and patellar tendons showed a normal echographic pattern in 58 athletes, and sonographic abnormalities in 15. The athletes with ultrasonographic alterations, compared to those with normal US picture, showed significantly higher U-Carr levels (p = 0.000), body mass index (BMI) values (p = 0.03) and were older (p = 0.005). The difference in U-Carr values among the subjects remained significant also after adjustment for age and BMI.Conclusion The results of the present study support the hypothesis that oxidative substances, also increased at systemic and not only at local level, may favor tendon damage.Level of Evidence IV (pilot study).
Keywords: Achilles tendon; soccer; oxydative stress; patellar tendon; ultrasonography